2002
DOI: 10.1016/s0377-0273(01)00260-8
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosity of rhyolite-vapor emulsions at magmatic temperatures by concentric cylinder rheometry

Abstract: The viscosity of natural rhyolitic melt from Lipari, Aeolian Islands and melt-bubble emulsions (30^50 vol% porosity) generated from Lipari rhyolite have been measured in a concentric cylinder rheometer at temperatures and shear rates in the range 925^1150 ‡C and 10 33^1 0 31:2 s 31 , respectively, in order to better understand the dependence of emulsion shear viscosity on temperature and shear rate in natural systems. Bubble-free melt exhibits Newtonian rrhenian behavior in the temperature range 950^1150 ‡C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 39 publications
2
52
0
1
Order By: Relevance
“…These bubbles behave like rigid particles, causing an increase in magma viscosity. Stein and Spera [2002] summarized the situation as follows: when Ca > 10, magma viscosity is decreased by bubbles; however, when Ca < 0.1, it is increased.…”
Section: The Effects Of Preeruptive Bubblesmentioning
confidence: 99%
“…These bubbles behave like rigid particles, causing an increase in magma viscosity. Stein and Spera [2002] summarized the situation as follows: when Ca > 10, magma viscosity is decreased by bubbles; however, when Ca < 0.1, it is increased.…”
Section: The Effects Of Preeruptive Bubblesmentioning
confidence: 99%
“…The presence of bubbles can either increase or decrease the viscosity of a suspension depending on the dynamic regime (Manga et al, 1998;Stein and Spera, 2002;Llewellin et al, 2002;Rust and Manga, 2002;Llewellin and Manga, 2005). Similarly to solid particles, bubbles deform flow lines within the suspending medium, which tends to increase the viscosity.…”
mentioning
confidence: 99%
“…The decreasing apparent viscosity of a bubbly material below the viscosity of the material itself has already been observed for viscous fluids like magmas or melt glass and polymers (Manga and Loewenberg, 2001;Llewellin et al, 2002;Rust and Manga, 2002;Stein and Spera, 2002;Bagdassarov and Pinkerton, 2003;Tuladhar and Mackley, 2005). These studies have shown that this behaviour is due to Viscosity ratio of a Canadian heavy oil saturated in methane and depressurized instantaneously from 30 bars to room pressure at different shear rates.…”
Section: Depletion Under Shearmentioning
confidence: 63%